Interrupting the Conversation: Implications for Crosstalk Between Viral and Bacterial Infections in the Asthmatic Airway - Ackland, Jodie; Watson, Alastair; Wilkinson, Tom M. A.; Staples, Karl J. (Frontiers in Allergy, 2021)
Asthma is a chronic heterogeneous respiratory disease affecting 300 million people and is thought to be driven by different inflammatory endotypes influenced by a myriad of genetic and environmental factors. The complexity of asthma has rendered it challenging to develop preventative and disease modifying therapies and it remains an unmet clinical need. Whilst many factors have been implicated in asthma pathogenesis and exacerbations, evidence indicates a prominent role of respiratory viruses. However, advances in culture-independent detection methods and extensive microbial profiling of the lung, have also demonstrated a role for respiratory bacteria in asthma. In particular, airway colonization by the Proteobacteria species Nontypeable Haemophilus influenzae (NTHi) and Moraxella catarrhalis (Mcat) is associated with increased risk of developing recurrent wheeze and asthma in early life, poor clinical outcomes in established adult asthma and the development of more severe inflammatory phenotypes. Furthermore, emerging evidence indicates that bacterial-viral interactions may influence exacerbation risk and disease severity, highlighting the need to consider the impact chronic airway colonisation by respiratory bacteria has on influencing host responses to viral infection. In this review, we first outline the currently understood role of viral and bacterial infections in precipitating asthma exacerbations and discuss the underappreciated potential impact of bacteria-virus crosstalk in modulating host responses. We discuss the mechanisms by which early life infection may predispose to asthma development. Finally, we consider how infection and persistent airway colonization may drive different asthma phenotypes, with a view to identifying pathophysiological mechanisms that may prove tractable to new treatment modalities.